Industrialization, FDI Inflow and Climate Change in Africa: A Scenario Analysis - Muhammad ALI; Emmanuel O. AWE; Salam S. MOHAMMED; Kazeem O. ISAH (Chinese Journal of Urban and Environmental Studies, 2024)
Despite their promises of wealth creation, productivity increase, and improved living circumstances in Africa, industrialization, and foreign direct investment (FDI) inflows have the potential to endanger the continent’s climate, particularly given the nature of energy intensity and associated emissions connected with their expansion. Thus, this study empirically examined the extent to which industrialization and FDI inflows contribute to the predictability of climate change in Africa, focusing on the top 10 greenhouse gas (GHG) emitting countries on the continent with data spanning from 1990 to 2023. Employing a bias-adjusted ordinary least square estimation technique, we considered both in-sample and out-of-sample forecasts that include several scenario analyses. We reveal both industrialization and FDI inflows as significant predictors of climate change in Africa but with varying degrees of environmental threats. This provides the foundation for, among other things, the suggestion that African continental and sub-regional bodies consider the need for differences in climate commitment strategies across the region based on the varying nature and magnitude of manufacturing intensity and FDI inflows, as well as associated GHG emissions and the nature of climate change vulnerability.